2020
DOI: 10.1186/s12916-020-01612-y
|View full text |Cite
|
Sign up to set email alerts
|

An evidence mapping and analysis of registered COVID-19 clinical trials in China

Abstract: Background: This article aims to summarize the key characteristics of registered trials of 2019 novel coronavirus (COVID-19), in terms of their spatial and temporal distributions, types of design and interventions, and patient characteristics among others. Methods: A comprehensive search of the registered COVID-19 trials has been performed on platforms including ClinicalTrials.gov, WHO International Clinical Trials Registry Platform (WHO ICTRP), Chinese Clinical Trials Registry (CHiCTR), Australian Clinical Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…More than ever, unproductive competition and opportunism should be avoided [ 20 , 34 ] to publish relevant, rigorous, and reliable research [ 39 ]. Collaborations should be promoted and systematic reviews with regular updates are also urgently required for the health practitioners to gain a comprehensive understanding of the issues concerned [ 5 , 33 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…More than ever, unproductive competition and opportunism should be avoided [ 20 , 34 ] to publish relevant, rigorous, and reliable research [ 39 ]. Collaborations should be promoted and systematic reviews with regular updates are also urgently required for the health practitioners to gain a comprehensive understanding of the issues concerned [ 5 , 33 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…TCM and biological agents are frequently used in registered COVID-19 clinical trials in China [8] . We have found that treatments that combine Chinese and Western medicine provide clues for managing COVID-19 patients in the Shanghai Public Health Clinical Center [9] .…”
Section: Discussionmentioning
confidence: 99%
“…The global scientific response, although highly collaborative in spirit, appears fragmented and disorganized. This is perhaps best illustrated by premature enthusiastic response to early studies from China and France 28,29 followed by the study reported by Mehra et al 50 In an effort to find a therapeutic agent to fight COVID‐19, a large number of clinical trials have proliferated 84‐88 but these trials vary widely in their design, target population and its stratification, indication, exclusion criteria, sample size, drugs and their dosing regimen, duration of therapy and study endpoints. An analysis of 201 trials registered before 26 March this year concluded that a third of these exclude clinical endpoints, almost half were designed to recruit 100 patients or less and more than 70% were open label, thus limiting their long‐term usefulness 89 .…”
Section: Discussionmentioning
confidence: 99%